Enhancing bioactive stability and applications: microencapsulation in fruit and vegetable waste valorization - Om Sunil Ingale; Bora Priya Pravin; Prashant Anil Pawase; Rafiya Shams; Kshirod Kumar Dash; Omar Bashir; Swarup Roy (Discover Food)
Abstract The large volumes of waste generated during fruit and vegetable processing pose environmental challenges but also serve as a valuable source of bioactive compounds (BCs), including polyphenols, carotenoids, and flavonoids, which have significant medicinal and nutritional applications. This article reviews emerging valorization strategies for fruit and vegetable waste (FVW), focusing on microencapsulation methods that stabilize, protect, and deliver these bioactive molecules. Microencapsulation not only enhances the bioavailability (BA), controlled release, and functional stability of BCs but also facilitates their integration into functional foods (FFs) and nutraceuticals through technologies like spray drying (SD) and freeze drying (FD). These BCs exhibit high retention and encapsulation efficiency (EE), thus opening their prospects for applications in the food and pharmaceutical sectors. However, major challenges still exist in the valorization of FVW, such as rapid degradation, scalability, high production costs, and heterogeneity of waste composition. Future developments in encapsulation processes, nanotechnology, and bioconversion present promising avenues for the improvement of stability and industrial applicability. Overcoming these challenges through green and innovative approaches will not only enhance the commercial value of FVW-derived bioactives but also provide a circular economy with substantial environmental and health impacts.